Factors Predicting Preventive Behaviors for Knee Osteoarthritis among Older Adults in Somdet District Kalasin Province - Sukserm, Thanoosin; Suwannarong, Bussakorn; Saengprajak, Nittaya (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
The objectives of the study were to study knee osteoarthritis preventive behaviors and factors predicting knee osteoarthritis preventive behaviors among older adults in Somdet District Kalasin Province. About 329 older adults were collected the data. It is calculated from the mean estimation formula. In the case of knowing the size of the population and proportional stratified random sampling. The questionnaire was used to collect the data. Analyzed data using frequency, percentage, mean, standard deviation, and stepwise multiple regression. The results found that knee osteoarthritis preventive behaviors were good level ( = 2.17, S.D. = 0.24) and self-efficacy to knee osteoarthritis preventive behaviors, knowledge about Knee osteoarthritis and sex female were capable of predicting 75.30% of knee osteoarthritis preventive behavior of older adults (Adjusted R = 0.750, P < 0.001). The factors with the highest influence as a predictive factor were perceived self-efficacy to knee osteoarthritis preventive behaviors (ß = 0.752, P < 0.001) knowledge about knee osteoarthritis (ß = 0.193, P < 0.001) sex female (ß = 0.064, P < 0.05). The results suggested that it should be promoted education and advocate self-confidence. Appropriate activities to help the elderly to be confident in expressing appropriate health behaviors were recommended to design. There might help the elderly to have behaviors to prevent osteoarthritis continuously and sustainably.